A 348-base-pair region in the latency-associated transcript facilitates herpes simplex virus type 1 reactivation. - Bloom, D C (1996)
Latency-associated transcript (LAT) promoter deletion mutants of herpes simplex virus type 1 have a reduced capacity to reactivate following adrenergic induction in the rabbit eye model. We have mapped a reactivation phenotype within LAT and describe the construction of recombinants in which poly(A) addition sites have been placed at intervals within the LAT region to form truncated LAT transcripts. These mutants localize the induced reactivation phenotype to the 5' end of LAT. To further define this region, we constructed a recombinant containing a 348-bp deletion located 217 bp downstream of the transcription start site of the 8.5-kb LAT. This virus, 17delta348, expresses LAT but exhibits a significantly reduced ability to reactivate following epinephrine iontophoresis into the cornea. Quantitative DNA PCR analysis reveals that 17delta 348 establishes a latent infection within rabbit trigeminal ganglia with the same efficiency as does either the rescuant or wild-type virus. The region deleted in 17delta348 encodes three potential translational initiators (ATGs) which we have mutated and demonstrated to be dispensable for epinephrine-induced reactivation. In addition, three smaller deletions within this region have been constructed and were shown to reactivate at wild-type (parent) frequencies. These studies indicate that an undefined portion of the 348-bp region is required to facilitate induced reactivation. Sequence analysis of this 348-bp region revealed a CpG island which extends into the LAT promoter and which possesses homology to conserved elements within the mouse and human XIST transcript encoded on the X chromosome. Possible implications of these elements in the regulation of LAT expression are discussed.